More Poet than Policeman: Newman and Education "in a large sense of the word" = Más poeta que policía : Newman y la educación "en un sentido amplio del término" - Shrimpton, Paul (Scripta theologica, 2019)
Thinkers such as MacIntyre affirm the importance of Newman’s educational classic The idea of a university in reminding the university about its nature and purpose. But Newman has a wider view of education: in his educational writings and practice he draws attention to those aspects of the university which contribute to its well-being. He focuses especially on its pastoral dimension, the nurturing of virtuous and fully-formed individuals by means of living arrangements, tutoring systems which provide individual guidance on the art of living well, and the genius loci of the institution.